A review of engraftment assessments following fecal microbiota transplant - Chloe Herman; Bridget M. Barker; Thais F. Bartelli; Vidhi Chandra; Rosa Krajmalnik-Brown; Mary Jewell; Le Li; Chen Liao; Florencia McAllister; Khemlal Nirmalkar; Joao B. Xavier; J. Gregory Caporaso (Gut Microbes)
Fecal Microbiota Transplant (FMT) is a treatment for recurrent Clostridium difficile infections and is being explored for other clinical applications, from alleviating digestive and neurological disorders, to restoring microbiomes impacted by cancer treatment. Quantifying the extent of engraftment following an FMT is important in understanding a recipient’s response to treatment. Engraftment and clinical response need to be investigated independently to evaluate an FMT’s role (or lack thereof) in achieving a clinical response. Standardized bioinformatics methodologies for quantifying engraftment extent would not only improve assessment and understanding of FMT outcomes, but also facilitate comparison of FMT results and protocols across studies. Here we review FMT studies, integrating three concepts from microbial ecology as framework to discuss how these studies approached assessing engraftment extent: 1) Community Coalescence investigates microbiome shifts following FMT engraftment, 2) Indicator Features tracks specific microbiome features as a signal of engraftment, and 3) Resilience examines how resistant post-FMT recipients’ microbiomes are to reverting back to baseline. These concepts explore subtly different questions about the microbiome following FMT. Taken together, they provide holistic insight into how an FMT alters a recipient’s microbiome composition and provide a clear framework for quantifying and communicating about microbiome engraftment.